Outranking multi-criteria methods - Podvezko, Valentinas (Lietuvos matematikos rinkinys, 2012)
In the realm of used worldwide multicriteria decision aid methods the two families of methods PROMETHEE and ELECTRE could be distinguished. These methods are rarely used and scarcely known in Lithuania. The methods create rankings of alternatives in accordance with priority levels of each alternative. The methods if different in details use the same core idea: a cumulative criterion comprises values of criteria and their weights indirectly by transforming such values with proprietary priority concordance and discordance indices. In the paper the methods PROMETHEE II and ELECTRE III are compared, their particularities and differences are outlined and discussed. Both methods are utilised for comparison of given alternatives.
Keywords: multi-criteria methods; PROMETHEE II and ELECTRE III methods; ranking of alternatives